Basis for the Management of Schistocerca cancellata (Orthoptera: Acrididae) - Birkhan, Júlia; Carrizo, Beatriz Noemi; Socias, Maria Guillermina; Costa, Maria Kátia Matiotti da; Guedes, Jerson Carus; Garcia, Flávio Roberto Mello (Oxford Academic Press, 2022)
The locust species Schistocerca cancellata Serville, endemic to South America, is known for its ability to form dense swarms, which reach the status of agricultural pest for several crops in southern South America. This article aimed to gather more accurate information about the history, biology, ecology, and control of S. cancellata, because of the 2021 invasions, which threatened to invade the Brazilian territory. During outbreak periods, swarms consume any available vegetation in the occurrence areas of Argentina, Brazil, Paraguay, Uruguay, Chile, and Bolivia. These invasions have been well documented in history, since they left deep marks wherever they went, especially in Argentina, which to this day represents the country that most accounted for agricultural losses from outbreaks. economy’s main current means of control are based on pesticides, whose chemical composition induces a series of damages to health, the environment, and consequently the ecosystem. Knowing about the biological processes of this locust is an important factor in understanding how swarms form, as well as controlling them. The intergovernmental coalition shows positive results in monitoring and controlling the swarms, which, even demonstrating stability, remain under constant surveillance by competent bodies.